COMPOSITION FEATURES OF KYRGYZ SONGS (BASED ON THE MELODY OF TOKTOGUL «TOGUZ KAYRYK») (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the features of the compositional structure of Kyrgyz kyus for komuz, as well as the features of the organization of internal structures, methods of variable changes in motives and principles of development. The object of analysis is the famous kyus by Toktogul Satylganov «Toguz kayryk». The first section of the article draws attention to the assessment of the researcher-ethnographer A. Zatevich, who was the first to notate this work by Toktogul, as well as to the analytical statements of the musicologist V. Vinogradov, who thoroughly studied the work of the Kyrgyz musician. The main section of the article contains an analysis of the main motivic-thematic structures and all their possible modifications during the development of the musical texture. The next section examines the place of each motive in the structure of the work, as well as their compositional functions, the principles of their alternation, and in connection with this, the established features of the compositional structure of the entire work. The penultimate section provides a comparative analysis of all the motive-thematic structures of the work and reveals their close interrelation and origin from one main motive. The final section draws attention to the national principles of forming kyuu for komuz, the principles of developing the main motive-thematic structures, the principles of their variation. Thus, the features of the compositional structure of works by folk musicians are noted, which are formed from the very compositional techniques they use.
Keywords: күү; кайрык; композиция; үнкурам; комуз толгоосу; кайрык түрлөрү; чыңалуу (кульминация); кайрыктар милдети (функция мотивов); үнжүрүш; үнсеки жылыштары (модуляциялар); четтөө.